47th AIAA Aerospace Sciences Meeting Including the New Horizons Forum and Aerospace Exposition 2009
DOI: 10.2514/6.2009-629
|View full text |Cite
|
Sign up to set email alerts
|

Automation of Design and Prototyping of Micro Aerial Vehicle

Abstract: The presented work is centered on the automation of the design process of Micro or Mini Aerial Vehicles (MAV). A design optimization framework that links together a CAD system for airframe design and a panel code for aerodynamic evaluations has been developed. This paper is based on research and results previously published by the research team. It describes the experiences made so far, and demonstrates with a case study, how fully automated design is indeed possible. The user is required to enter the initial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…153,154 For example, the plates manufactured by FDM technology possess better strength in x, y direction as compared to the strength in z-direction (build direction). 155,156…”
Section: Anisotropic In Mechanical Properties and Microstructurementioning
confidence: 99%
“…153,154 For example, the plates manufactured by FDM technology possess better strength in x, y direction as compared to the strength in z-direction (build direction). 155,156…”
Section: Anisotropic In Mechanical Properties and Microstructurementioning
confidence: 99%
“…The intention was to develop a methodology that uses commercial off-the-shelf (COTS) components as far as possible and that, in addition to the aerodynamic optimization, also takes into account internal component placement and longitudinal stability. This was achieved through the development of a design automation framework of interconnected computer analysis tools [8][9][10][11]. The system includes geometry, aerodynamics, and performance modelling.…”
Section: Distributed Design Frameworkmentioning
confidence: 99%
“…The optimization problem to be solved is rather complex, and previous studies [10,11] have shown that the MOGA-II [23] algorithm struggles to search the whole design space efficiently. One serious issue observed was that the GA had a tendency to collapse its search in the lower left corner of the Endurance Vs.…”
Section: Optimization Strategy Refinementsmentioning
confidence: 99%
“…The assumption was that increasing wind and turbulence would result in a noticeable change in performance. In addition to evaluating the relative effect of turbulence, the flight tests was also intended to provide absolute data for latter evaluation of MAV performance prediction methods as part of the authors' on-going research in MAV design automation [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…They calibrated thrust as a function of velocity and motor input power. Considering that electric motor efficiency is coupled to motor temperature [9], it was decided for these tests to use the more common method of calibrating propeller characteristics as a function of rpm and velocity.…”
Section: Introductionmentioning
confidence: 99%